A dynamic control for snowboard multibody models - Casolo, F.; Cinquemani, S.; Cocetta, M.; Lorenzi, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: One aim of the snowboard dynamic Simulation is the optimization of the snowboarder movement in order to obtain a preset trajectory on the slope moving the board äs fast äs possible and to chose, among those available, the board with the more suitable mechanical characteristics. This preliminary work is mainly focused on the model of board-snow contact and on the development of a robust control system capable of maintaining the board on a given trajectory,